Service quality and economic performance in the US airline business. Issue 3 (3rd July 2017) - Kalemba, Nicole; Campa-Planas, Fernando; Hernández-Lara, Ana-Beatriz; Sánchez-Rebull, Maria Victória
Abstract: The purpose of this paper is to determine the effects of service quality on US airlines' economic performance. In order to cover this goal, four quality indexes related to the airline industry, and two economic performance indicators, revenues and return on investment (ROI), have been considered. Data from American airline companies from 2006 to 2013 have been used to determine if airlines' profitability increases when service quality improves. Considering the effects on airlines' profitability, the results confirm the positive and significant influence of service quality on the ROI of the US airline companies. A non-significant effect was found for airline revenues in relation to quality. No previous research in this area has been done so these findings could encourage airline companies to invest in quality, since this policy can have a positive return on their profitability.